A vector-based algorithm to generate and update multiplicatively weighted Voronoi diagrams for points, polylines, and polygons - Gong, Yongxi; Li, Guicai; Tian, Yuan; Lin, Yaoyu; Liu, Yu (Computers & geosciences, 2012)
A Voronoi diagram is a basic data structure in geometry with many applications. Existing research studies have focused on ordinary Voronoi diagrams, and some vector-based algorithms have been developed to generate multiplicatively weighted Voronoi diagrams (MWVDs) for points. An algorithm to construct MWVDs for points, polylines, and polygons is raster-based and has drawbacks. We propose a vector-based algorithm to generate and update MWVDs for points, polylines, and polygons. The MWVDs of two sites characterize the geometric features of multiplicatively weighted Voronoi regions, and the algorithm for Boolean operations on conic polygons is the computational preliminary to the MWVDs of N sites. The proposed algorithm is vector-based and can deal with sites with mixed spatial extents and various weights. We implement the algorithm in C# and present several examples of generating and updating MWVDs. ► We develop an algorithm to generate MWVDs for sites with mixed spatial extents. ► The method is vector-based and can explore the shape characteristic of the MWVDs. ► The method can generate both MWVDs and OVDs, and degeneration cases are considered. ► The method is accurate than raster-based method and is efficient for GIS applications.